TELAAH HADITS KEUTAMAAN DAN URGENSI MENUNTUT ILMU DI ERA DIGITAL: RELEVANSI DENGAN TANTANGAN PENDIDIKAN MODERN DAN KRITERIA PENDIDIK IDEAL - Agustina Tarik, Atika; Kurjum, Muhammad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This study aims to determine how the existence of the study of hadith science on the virtues and urgency of seeking knowledge in the digital era can be used in the application of principles in modern education today. Knowledge is an obligation that will always be attached to a Muslim. Because it can be seen that seeking knowledge is part of worship. The research method used is library research with a historical approach and hadith science, including criticism of sanad and matan to analyze the validity of related hadiths. This study utilizes sources from Maktabah Syamilah and other literature such as books, journals, and articles. Through research with this method, it can be found that the hadith of the Prophet has emphasized the importance of seeking knowledge for every Muslim. However, in the current digital era, where information is easily accessible to anyone, it certainly becomes an awareness for ourselves to need a more critical approach in filtering and utilizing knowledge. In addition, this study discusses the ideal criteria for an educator in the digital era, which include the ability to use technology wisely, assess information critically, and guide students in dealing with social and technological changes. Another thing that is a point of discovery in this study is that the principles of the Hadith of the Prophet can provide solutions to the challenges of education in the modern era today.